2012
DOI: 10.5897/jmpr11.1710
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salt stress on growth, pigments, soluble sugars and ion accumulation in three pistachio cultivars

Abstract: In this study, three pistachio cultivars were treated with different concentration of salt solution to provide a reference for the cultivation of salt tolerant rootstocks. The results revealed that increasing the salinity stress resulted in decreasing growth performances of the plants in the three pistachio cultivars. This decrease was not significant in salinity of 100 mM but was significant in other salinities compared to control. In all salinity levels and control conditions, Akbari (Ak) cultivar exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…Under saline conditions, accumulation of Na + in shoots and roots was observed in the studied rootstocks. The Na + accumulation in shoots was higher than the roots in all three rootstocks, which was consistent with the results of previous studies [44,51,52]. Accumulation of sodium in plant tissues in salt-sensitive species is greater than in tolerant ones.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Under saline conditions, accumulation of Na + in shoots and roots was observed in the studied rootstocks. The Na + accumulation in shoots was higher than the roots in all three rootstocks, which was consistent with the results of previous studies [44,51,52]. Accumulation of sodium in plant tissues in salt-sensitive species is greater than in tolerant ones.…”
Section: Discussionsupporting
confidence: 92%
“…Changes in concentrations of pigments under salt stress can be used as a biochemical marker for selecting salinity-tolerant rootstocks [44,45]. In the present study, a significant decrease was observed in the amount of chlorophylls (a, a/b and total) with increasing salinity.…”
Section: Discussionsupporting
confidence: 55%
“…The reduction of tree growth associated with salinity stress in pistachio was documented by several authors in previous studies [7,68,69]. Under lower soil osmotic potential, trees spend more metabolic energy (photosynthate) synthesizing and concentrating carbohydrates to adjust osmotically [70], which in turn adversely affects the vegetative growth and yield [22,23,71,72].…”
Section: Discussionmentioning
confidence: 94%
“…The fluctuation in this study under salt stress might be caused by the changes of CO 2 assimilation, source-sink carbon partitioning, and/ or the activity of related enzymes [ 34 ]. Soluble proteins in AVF clearly increased depending on the rising of NaCl, and then significantly reduced, indicating that cell turgor maintaining and water acquisition regulation perhaps was affected by salt stress [ 35 , 36 ]. The results were consistent with the literature reported on Salvia miltiorrhiza [ 37 ].…”
Section: Discussionmentioning
confidence: 99%